Upaya Meningkatkan Motivasi Belajar dan Pemahaman Matematika Siswa pada Materi Statistika Melalui Model Pembelajaran Kooperatif Tipe Teams Assisted Individualization (TAI) Kelas XII IPS 1 Semester Ganjil SMA Negeri 5 Kota Jambi Tahun Pelajaran 2019/2020 - Betty Panjaitan (Jurnal Ilmiah Dikdaya, 2020)
This study aims to improve student motivation and students' understanding of mathematics through the application of the Teams Assited Individualization (TAI) learning model Class XII IPS 1 odd semester of SMA N 5 Kota Jambi Academic Year 2019/2020. This research is a Classroom Action Research conducted in 3 cycles. Each cycle consists of 4 stages, namely planning, action, observation, and reflection. The subject of the research was Class XII IPS 1 odd semester of SMA N 5 Kota Jambi in the academic year 2019/2020 where the researcher was a mathematics teacher in the class. The research data was obtained through observation, questionnaires, and tests. The data analysis technique is comparative descriptive analysis technique. The results of the study concluded that the implementation of classroom action through the TAI (Teams Assisted Individualization) cooperative learning model on statistical material Class XII IPS 1 odd semester of SMA N 5 Kota Jambi Academic Year 2019/2020 could increase students' motivation and understanding of mathematics. From the results of observations of student motivation to increase motivation to learn mathematics from the original low to quite high. Whereas for the understanding of mathematics in the first cycle, the average score of the final test of the student cycle was 65.1 and the percentage of students who had grades above the KKM reached 44.44%. In cycle II, the average value of the final test of the student cycle was 70.7 and the percentage of students who had grades above the KKM increased by 22.23% from the first cycle which reached 66.67%. In cycle III, the average value of the final test of the student cycle is 78.4 and the percentage of students who have grades above the KKM is 75%. Therefore, it is suggested to the teacher to be able to apply the TAI type of cooperative learning model to learning in the classroom.